2020
DOI: 10.1038/s41529-020-00135-4
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and nanomechanical changes in tungsten in high heat flux conditions

Abstract: Morphological and nanomechanical alteration of tungsten in extreme environments, like those in edge localized modes in nuclear fusion environments, up to 46.3 GWm−2 heat fluxes were experimentally simulated using electrothermal plasma. Surface and subsurface damage to the tungsten is seen mainly in the form of pore formation, cracks, and resolidified melt instabilities. Mirco voids, rosette-type microfeatures, core-shell structure, particle enrichment, and submicron channels all manifest in the damaged subsurf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…In our previous studies, we identified stress-driven surface diffusion as the primary driving force for nanotendril growth at the early stage of plasma exposure, where the stress is developed in the nearsurface layer of plasma-facing component (PFC) tungsten due to over-pressurized nanometer-size bubbles formed by the implanted helium ions in the PFC material. These nanotendrils are the precursor to the surface nanostructure that eventually grows to form the fuzz-like structure on the PFC surface [5,8,[23][24][25]. Additionally, subsurface bubble dynamics [26][27][28][29][30], dislocation loop punching [17,31,32], bubble bursting, and surface crater formation [17,[33][34][35] play important roles in the early stages of the nanotendril growth process.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, we identified stress-driven surface diffusion as the primary driving force for nanotendril growth at the early stage of plasma exposure, where the stress is developed in the nearsurface layer of plasma-facing component (PFC) tungsten due to over-pressurized nanometer-size bubbles formed by the implanted helium ions in the PFC material. These nanotendrils are the precursor to the surface nanostructure that eventually grows to form the fuzz-like structure on the PFC surface [5,8,[23][24][25]. Additionally, subsurface bubble dynamics [26][27][28][29][30], dislocation loop punching [17,31,32], bubble bursting, and surface crater formation [17,[33][34][35] play important roles in the early stages of the nanotendril growth process.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding to the ions for the experiments, we chose hydrogen and helium ions. For the hydrogen ions, we chose deuterium and tritium ions, while for the helium ion, we chose 4-He, sincesd these three ions are the three most important ions in the fusion reaction [8][9][10]. For our experimental data, we chose two microns as our material thickness.…”
Section: Methodsmentioning
confidence: 99%